Advances in Treatment of Wilson Disease. (28th February 2018) - Aggarwal, Annu; Bhatt, Mohit
Background: Wilson disease (WD) is an inherited neurometabolic disorder that results in excessive copper deposition in the liver and the brain, affecting children and young adults. Without treatment the disease is invariably fatal. Though treatments for WD have been available since the 1950s, the disease continues to be associated with considerable morbidity and mortality because of missed diagnosis, and delayed or inadequate treatment. In this paper we survey WD-related literature in order to review recent advances in WD treatment. Methods: We performed a literature search using the PubMed database for articles relating to WD and its medical treatment. We reviewed the articles, and cross-references of relevant articles, to summarize the current practices for treatment of WD. Results: The survey shows that if WD is properly treated, in most patients the liver can be stabilized, even severe neurological disability reversed, and patients can resume normal lives. Discussion: Medical treatment for WD includes use of copper chelators (penicillamine, trientine, dimercaprol, dimercaptopropane sulfonate, and ammonium tetrathiomolybdate) and drugs that decrease gastrointestinal copper absorption. Our knowledge of the treatment approaches has benefited from the large systematic clinical studies that have been conducted over the last decade. For each drug used to treat WD, we surveyed its development, indication for use, dosing, efficacy, and adverse effects.